2020
DOI: 10.3389/fvets.2020.00319
|View full text |Cite|
|
Sign up to set email alerts
|

Understanding Tick Biology and Its Implications in Anti-tick and Transmission Blocking Vaccines Against Tick-Borne Pathogens

Abstract: Ticks are obligate blood-feeding ectoparasites that transmit a wide variety of pathogens to animals and humans in many parts of the world. Currently, tick control methods primarily rely on the application of chemical acaricides, which results in the development of resistance among tick populations and environmental contamination. Therefore, an alternative tick control method, such as vaccines have been shown to be a feasible strategy that offers a sustainable, safe, effective, and environment-friendly solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 104 publications
2
40
0
Order By: Relevance
“…46,47 Cross-reactivity with Bm86 proteins from Rhipicephalus (Boophilus) decoloratus has been reported, with a significant decrease in mean weight of ticks and egg masses per tick, 48 and two Bm86 homologues have been developed based on the Rhipicephalus (Boophilus) annulatus (Ba86) and Hyaloma anatolicum anatolicum (Haa86) ticks. 10 Vaccination of cattle with Bm86 induced anti-Bm86 antibodies that induced lysis of tick gut cells leading to higher mortality rates in ticks and reduction in weights and egg laying capacity of ticks that completed feeding. 46,47,49 Field trials confirmed that vaccination with Bm86 was able to control Rhipicephalus (Boophilus) microplus populations in grazing cattle, with the greatest effect observed on fertility leading to progressive control of tick numbers in progressive populations.…”
Section: Vaccines Targeting Tick Feeding and Water Homeostasismentioning
confidence: 99%
See 1 more Smart Citation
“…46,47 Cross-reactivity with Bm86 proteins from Rhipicephalus (Boophilus) decoloratus has been reported, with a significant decrease in mean weight of ticks and egg masses per tick, 48 and two Bm86 homologues have been developed based on the Rhipicephalus (Boophilus) annulatus (Ba86) and Hyaloma anatolicum anatolicum (Haa86) ticks. 10 Vaccination of cattle with Bm86 induced anti-Bm86 antibodies that induced lysis of tick gut cells leading to higher mortality rates in ticks and reduction in weights and egg laying capacity of ticks that completed feeding. 46,47,49 Field trials confirmed that vaccination with Bm86 was able to control Rhipicephalus (Boophilus) microplus populations in grazing cattle, with the greatest effect observed on fertility leading to progressive control of tick numbers in progressive populations.…”
Section: Vaccines Targeting Tick Feeding and Water Homeostasismentioning
confidence: 99%
“…For example, inhibition of NK target cell binding, type I interferon production, and suppression of complement activation by tick saliva can support tick-borne pathogen transmission and pathogens themselves can inhibit host responses to facilitate pathogen survival and multiplication. 2,3,[7][8][9][10] This delicate balance between defence and survival mechanisms within pathogens, ticks and hosts has been extensively studied and lead to a better understanding of the immune modulators involved and the emergence of potential candidates for anti-tick and pathogen transmission blocking vaccines. As host antibodies generated through either exposure or vaccination have been shown to successfully be absorbed in the tick blood meal and pass into the haemolymph, while maintaining their ability to bind antigens, [11][12][13] vaccination of hosts presents an opportunity to target both ticks and tick-borne pathogens.…”
Section: Introduction To Ti Ck-hos T-pathog En Inter Ac Ti On Smentioning
confidence: 99%
“…Such vaccines interfere with pathogen transmission and have been developed in animal models for diseases transmitted by fleas, lice, mosquitoes, ticks and sand flies. 68,70,[72][73][74][75] Two foundational studies provided the basis for the development of tick-based vaccination. One used larval extract of Dermacentor variabilis to protect against infestation of guinea pigs, while the other demonstrated that repeated infestation of D. variabilis in rabbits prevented transmission of Francisella tularensis.…”
Section: Impli C Ati On S Of Ti Ck Hyper S Ens Itivit Y For De Velomentioning
confidence: 99%
“…They have a diversity of function that includes attachment to the host with cement-like protein, preventing coagulation of host blood, blocking the effects of oxidants and histamine and suppressing host immune responses against salivary proteins. 11,42,43,68,70,[72][73][74][75][76][77][78][79][87][88][89][90][91][92][93][94][95][96][97][98][99][100] The specific function and kinetics of salivary proteins are just beginning to be documented but it is clear that alteration of protein types during feeding and redundancy of function are common. Salivary proteins that promote tick feeding and pathogen transmission change during the 3 to 5 day tick feed, a process known as 'sialome switching'.…”
Section: Impli C Ati On S Of Ti Ck Hyper S Ens Itivit Y For De Velomentioning
confidence: 99%
See 1 more Smart Citation